Design of a Web-Based Citizen Complaint System in Increasing Citizen Participation in the Village Development Process - Ningrum, Diah Ayu Cahya; Riadi, Aditya Akbar; Susanto, Arief (Journal La Multiapp, 2025)
Jekulo Village faces challenges in managing citizen complaints and grievances due to limited physical infrastructure and time. The conventional complaint mechanism is often ineffective in accommodating citizen aspirations in a transparent and responsive manner. The manual complaint recording and resolution process also causes complaint handling to be slow and less organized. This paper aims to discuss the importance of implementing a web-based citizen complaint system to increase community participation in village development. This system is designed so that residents can submit complaints, grievances, and suggestions more easily and efficiently, while also allowing the village government to respond to complaints more quickly and accurately. With a technology-based system, communication between residents and the village government can run more transparently, and increase accountability in handling complaints. The results of the development of a web-based citizen complaint system in Jekulo Village show increased efficiency in handling public complaints. This system accelerates the process of receiving, verifying, and resolving citizen complaints, so that problems can be handled more quickly and accurately. In addition, transparency in resolving complaints increases, which has an impact on increasing citizen trust in the village government. With the real-time complaint status monitoring feature, residents feel more involved in the village development process. The system also provides data that can be analyzed to identify patterns of problems that often occur, so that village governments can take preventive steps to resolve recurring issues. Overall, the system is an effective tool in strengthening community participation and building villages that are more inclusive and responsive to the needs of their citizens.